Evaluation of non-invasive screening measures to identify individuals with prediabetes. Issue 1 (January 2015) - Vanderwood, Karl K; Kramer, Mary Kaye; Miller, Rachel G.; Arena, Vincent C.; Kriska, Andrea M.
Abstract Aims Because blood-based screening to identify those with prediabetes to take part in Diabetes Prevention Program (DPP) translation efforts can be costly and time-consuming, non-invasive methods are needed. The aims of this paper are to evaluate the ability of the American Diabetes Association (ADA) risk test in identifying individuals with prediabetes, as well as the use of body composition measures for this purpose. In addition the utility of these alternate methods to ascertain the presence of the metabolic syndrome was assessed. Methods Potential participants were recruited from a worksite and three community centers to take part in a DPP translation study. Participants completed onsite screening where anthropometric measures, fasting lipids and glucose, and hemoglobin A1c were assessed. Those with a BMI ≥24 kg/m2 and prediabetes and/or the metabolic syndrome were eligible to participate. Non-invasive screening methods were evaluated for their ability to identify those with prediabetes and the metabolic syndrome based on clinically measured values. Results All non-invasive methods were highly sensitive (68.9% to 98.5%) in the detection of prediabetes, but specificity was low (6.7% to 44.5%). None of the alternatives evaluated achieved acceptable discrimination levels in ROC analysis. Similar results were noted in identifying the metabolic syndrome. Conclusions The non-invasive methods evaluated in this study effectively identify participants with prediabetes, but would also allow for enrollment of a large number of individuals who do not have prediabetes. Deciding whether to use these alternatives, blood-based measures, or a combination of both will ultimately depend on the purpose of the program and the level of flexibility regarding participant eligibility.